Evaluation of detoxication arsenic salt solution by humates by biotesting - A. S. Konovalov (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
We investigated, toxicity and detoxification of model solutions of arsenic salts (Na3AsO4) by biotesting. Decreasing the toxicity of arsenic using humic substances («Powhumus», «Lignohumate», and «Humate-80») is shown. The possibility of use of humic substances to detoxify arsenic contamination, in model experiments is studied. To study the possibility of detoxification model contamination by salt of arsenic we used humic substances Powhumus (humate from leonardite «Humintech Ltd», Germany), Humate-80 (potassium, humate LLC «Agricultural Technology») and. Lignohumate (potassium, humate «SPA «RET»). As test objects seeds of Lepidium. sativum. L. (JSC «Irkutsk seeds») and. algae (Scenedesmus quadricauda (Turp.) Breb.) were taken. Toxicity was evaluated by effect on seed germination and. root length of L. sativum, the change in intensity of chlorophyll fluorescence of algae cells S. quadricauda. The significance of differences was determined, by Student's test. The table shows the mean values and. standard deviations for p > 0,95. Sodium arsenite at a concentration, of 8 mg/cdm inhibited seed germination of cress to 70,1 ± 6,9 %. The content of 9 mg/cdm. Na3AsO4 reduced, the number of germinated seeds to 75,1 ± 6,6 %. LC50 for this method was equal 5,7 mg/cdm. In applying the HS in a concentration, of 0,2 g/cdm a decrease toxicity of sodium arsenite to 25,3 ± 2,7 % was observed. The most effective model in reducing the toxicity of arsenic contamination was observed at a concentration of Powhumus 1,0 g/dm3 - the number of germinated, seeds was 90,1 ± 8,7 %. The next stage was the bioassay using the registration reducing chlorophyll fluorescence of algae cells S. quadricauda. Value of LC50 for this method was 1,5 mg/cdm. The concentration of sodium arsenite 1,8 and 1,5 mg/ cdm suppressed, levels of chlorophyll fluorescence by more than 30 % (the level of chlorophyll fluorescence was 26,4 ± 3,2 % and. 54,5 ± 6,1 % respectively). Powhumus in concentration of 0,05 g/cdm reduced toxicity of samples for 36,7 ± 3,9 % and. 31,8 ± 3,4 %, respectively. Bioassay method of changing the intensity of chlorophyll fluorescence of cells of algae S. quadricauda showed greater sensitivity and. speed of the response than the method of assessing the impact on seed, germination. and seedling root length of L. sativum.